We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive pseudonymised information about your use of our website. cookie policy and privacy policy.
 
+0  
 
+1
437
3
avatar

i*i= -1 right?

 Jul 25, 2017
 #1
avatar
0

Sqrt(-1) = i

i^2 =sqrt(-1) x sqrt(-1) = - 1 (you got it right)

i^3 = -1 x i = -i

i^4 =-1 x -1 = 1 Then the pattern repeats.

 Jul 25, 2017
 #2
avatar+7499 
0

Yup correct.

 Jul 25, 2017
 #3
avatar+20 
+2

\(\sqrt{-1}=i\)

\(i \times i = \sqrt{-1} \times \sqrt{-1} = {\sqrt{-1}}^{2} = -1\)

yes.

 Jul 26, 2017

7 Online Users